Agricultural Policies and Practices: Pathways for Transformation - Neupane, Hari Sharma; Acharya, Bikram; Pradeep; Gyawali, Buddhi Raj (Nepal Public Policy Review, 2025)
Agriculture has been a cornerstone of human civilization for thousands of years, providing food and other essential resources to sustain our societies. However, as we enter the 21st century, we face unprecedented challenges that threaten the very foundations of our agricultural systems. Climate change, resource depletion, and population growth are just a few of the issues that demand urgent attention from policymakers and practitioners alike. Further, the growing population, climate change, the recent COVID-19 pandemic, the Ukraine-Russia war, and the depreciation of national currencies have disrupted the global food supply chain and increased food prices and food insecurity in many countries, including Nepal. The Nepalese agriculture sector alone contributed employment opportunities for more than 60 % of the population with a 23.9% share in total value added of the national economy (Ministry of Finance, 2022). Though the majority of farmers in Nepal are engaged in the agriculture sector, there is still a dominance of traditional and subsistence agriculture and the country's agricultural production is not enough to feed its population. The continued rise in import bills and volume of food products in recent years has been a major challenge for the country. Addressing these constraints warrants consortia of efforts from the government, nonprofits, and private sectors to promote sustainable and regenerative agricultural concepts and practices that align with local farm attributes and the agroecological environment. With the above mentioned issue, Policy Research Institute, the publisher of NPPR, collaborated with Association of Nepalese Agricultural Professionals of Americas (NAPA) for the utilization of expert knowledge for public policy making and policy discussion. PRI is open to collaborating with any professional and intellectual society for policy issues. Thereof, a two-day (January 6-7, 2023) virtual symposium on "Agricultural Policies and Practices in Nepal: Pathways for Transformation" was jointly organized by the PRI and NAPA with the aim to discuss and synthesize structural, policy intervention-related procedural, and local barriers and issues inherent to inadequate agricultural growth in Nepal and recommend transformative and pragmatic policies, programs, and practices feasible at local, regional, and national levels. The other symposium collaborators were the Ministry of Agriculture and Livestock Development (MoALD), Nepal Agricultural Research Council (NARC), Agriculture and Forestry University (AFU), Institute of Agriculture and Animal Sciences (IAAS, Tribhuvan University), Nepal Agricultural Cooperative Central Federation Ltd. (NACCFL), and Society of Agricultural Scientists-Nepal (SAS-Nepal). The 38 papers presented at the symposium brought together over 500 researchers, policymakers, and practitioners from around the world. The symposium highlighted the importance of innovative policies and practices that can help transform agriculture and ensure its sustainability for future generations. The symposium was organized and facilitated in four thematic areas. The Agriculture Policy theme highlighted an analysis of current agricultural policies, laws, and regulations that have hindered the production and marketing of farm products, land use policies, transformative agriculture for the viable and circular economy, promoting cooperative farming, farm diversity, and sustainability including internationally successful policy practices suitable for Nepal. The Agricultural Research, Education, and Extension theme included diverse subject matters. These were genetic improvement of crops and livestock for diverse agro-climatic zones; technology innovations and dissemination; science-based knowledge and extension practices; climate-smart and organic agriculture; agri-business and entrepreneurship; commercial agriculture; and integration of agricultural research, education, and extension. Similarly, the Technology and Infrastructure Development theme focused on varied avenues of innovative technology (such as UAV, GIS, and Remote Sensing), farm mechanization, and smart and efficient irrigation practices to optimize costs of production, labor, fertilizer shortages, and monitoring of plant and soil health Finally, the Governance theme underpinned coherence and discordance between the policy frameworks and governing structures/mechanisms of three levels of government and opportunities for realignment for agricultural transformation as well as a local governance framework for agricultural service delivery at a municipality level. Finally, the symposium highlighted the importance of partnerships and collaborations in driving transformational change. The papers discussed the potential of public-private partnerships, multi-stakeholder platforms, and other forms of collaboration to leverage resources, share knowledge, and scale up innovative solutions. This special issue received 20 papers for publication consideration, however, after the review process, it is able to manage 12 papers for publication. These papers provide a rich and diverse set of insights into the pathways for transforming agriculture. They offer both practical guidance and theoretical frameworks for policymakers and practitioners seeking to navigate the complex challenges facing agriculture today. We hope this special issue will inspire further research and action towards a more sustainable and equitable agricultural future. We thank all the authors who contributed to this special issue and the reviewers who provided their valuable feedback. We also extend our appreciation to the symposium organizers and collaborators. Finally, we encourage additional authors/presenters to submit their papers in the NPPR’s Regular Issue, which will be published in September 2023.